. (March 2014) - Duarte, Mauricio
In Colombia, society has come to be organized in terms of a division between those with and those without links to narcotrafficking. This moral boundary recently experienced a symbolic disturbance with the entrance on the country's cultural scene of Andrés López López, a former Colombian drug trafficker, and his El cartel de los sapos (2008). An examination of the discursive and political strategies employed in this book, in which drug trafficking is referred to through the metaphor "bacteria, " allows us to understand the construction of a narrator who calls attention to the hypocrisy of the government and society regarding the reincorporation of narcotraffickers into civilian life while provoking a national debate on the difference between history and fiction. En Colombia, la sociedad ha llegado a organizarse en términos de una división entre aquellos que tienen y no vínculos con el narcotráfico. Este límite moral experimentó un reciente disturbio simbólico con la entrada de Andrés López López, un ex-narcotraficante colombiano, y su libro El cartel de los sapos (2008) en la escena cultural del país. Un análisis de las estrategias discursivas y políticas empleadas en este libro, en el que el tráfico de drogas se define a través de la metáfora de la "bacteria, " nos permite entender la construcción de un narrador que devela la hipocresía gubernamental y social con respecto a la reincorporación de los narcotraficantes en la vida civil al mismo tiempo que provoca un debate nacional sobre la diferencia entre historia y ficción.